#TITLE_ALTERNATIVE# - AJI (NIM 10102031), FATAH
Let G be a simple connected graph with V(G) as its vertex set. Suppose that S = {s1, s2, s3,..., sk} is a subset of V(G) and v is a vertex of V(G). A coordinate vector of v relative to S is defined as r(v | S) = (d(v, s1),d(v, s2),...,d(v, sk)) . S is said to be a resolving set if and only if for every v in V(G), the vector r(v | S) are distinct. Metric dimension of G is the minimum cardinality of all resolving sets of G. This final project discusses the method of determining metric dimension of any simple connected graph and, based on the method, develops an algorithm to be used in a computer program.